THE ROLE OF LEARNING TECHNOLOGY IN DEVELOPING A COMPETENCY-BASED CURRICULUM IN ISLAMIC EDUCATION. - Fadila, Ibnatun Intan (Educational Technology Journal, 2025)
The development of technology and information in the 21st century era has brought many significant changes to various fields, one of which is in the field of education including Islamic education. Its development has a major influence on life because technology is one of the important things in the application and development of competency-based curriculum so as to make it more relevant to the needs of students in the digital era. This article discusses the role of technology in supporting the development of a competency-based curriculum in the realm of Islamic education, by applying a foundation on how technology can be used to enhance students' knowledge skills, as well as Islamic values. The research found that learning technology enables better assessment than before, more interaction and collaboration, creates an active learning atmosphere, and creates greater access to various resources used for learning. Through this research, it is hoped that it can provide a change for an educator in making policy on how to design and implement a curriculum that is relevant to technological advances. The results are expected to help improve the quality of Islamic education to be more flexible and innovative.